Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.12924/cis2019.07010030
|View full text |Cite
|
Sign up to set email alerts
|

An Expert Elicitation of Public Acceptance of Renewable Energy in Kenya

Abstract: This article reports evidence for substantial public support for the large-scale deployment of three renewable energy options in Kenya: wind, solar PV, and geothermal energy. With these renewable technologies, the government of Kenya could make a large contribution to reaching its national commitment under the Paris Agreement. Prices, infrastructural needs, and land-use requirements importantly contribute to shaping public opinion about these renewable energy alternatives, in different ways and directions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We found that most SSA government actors in the energy sector engage in top-down approaches that superficially involve the public in validation workshops and interviews after project decisions are made [81][82][83]. Other top-down approaches are expert-centred in that experts are tasked with developing energy solutions with little or no participation from the communities they are designing for [11,77,82,83]. These top-down approaches, coupled with the structural inequalities rampant in SSA countries have hampered the transition towards more democratic and sustainable energy systems [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that most SSA government actors in the energy sector engage in top-down approaches that superficially involve the public in validation workshops and interviews after project decisions are made [81][82][83]. Other top-down approaches are expert-centred in that experts are tasked with developing energy solutions with little or no participation from the communities they are designing for [11,77,82,83]. These top-down approaches, coupled with the structural inequalities rampant in SSA countries have hampered the transition towards more democratic and sustainable energy systems [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…There was a consensus in the literature that local communities should be engaged from the onset to the end of the project. The table below summarizes the key arguments for stakeholder engagement in community projects in SSA [52,54,68,[72][73][74][75][76][77][78][79][80][81][82][83][84]. A co-design form of engagement was proposed by various authors as an effective strategy for engaging different stakeholders at all levels [52,54,80,81].…”
Section: Stakeholder Engagement In Energy Projects In Ssamentioning
confidence: 99%
“…Information-choice Questionnaires (ICQs) were originally developed to provide respondents with the necessary information to reach informed opinions about complex topics [34]. ICQs have been applied in the field of energy in recent years on the topics of Carbon Capture and Storage (CCS) [35][36][37] and renewable energy in Kenya [38]. Previous research on ICQs has shown that opinions change after information was provided, confirming the use of providing information prior to asking one's opinion on a topic which they have little knowledge about.…”
Section: Icqmentioning
confidence: 99%
“…This is a common issue across other SSA countries where government or elite organizations wholly own projects without transferring power to local communities [55,56,35,11,50,33]. This has resulted in limited community involvement through top-down approaches [17,[57][58][59], similar to those in the United States [17].…”
Section: Community Energy Governancementioning
confidence: 99%